Prospecção em tecnologia assistiva para alunos com surdez e cegueira no ensino superior : um estudo do futuro - Santos, Sandra de Andrade (2015)
The search includes two strategic themes for the contribution of technological and scientific development of the country: the Future Study and Assistive Technology resources to person with deafness and blindness with applicability for education, specifically for higher education, with the axis technology foresight connection. The objective was to conduct prospecting technology patents of TA resources worldwide to identify the position of Brazil as depositor of Assistive Technology. The methodology applied to technological forecasting was the literature review and the extrapolation of trends, such as methods of a Prospective Study in a conceptual approach to the Future Study. The study in patent applications in Assistive Technology for people with deafness and blindness occurred through data mining of a set of 1,241 patents. The data combined keywords Assistive Technology, person with deafness and blindness, education, method, software, products, major depositors, leading countries, organizations, key inventors, IPC codes and annual evolution. From these keywords figures were generated showing interest in the area of assistive technology, its technical and application by the world´s largest depositors. It was identified that the TA resources with applicability in higher education, according to the processing of data in VantagePoint tool, are not developed; we understand that this is because it is new terminology Assistive Technology in other areas of knowledge when compared to the area of education and the International Patent Classification (IPC) does not inform the patent by level of education, but by its technical nature and application. We understand that the term: Instructional Resources is still used for customers with disabilities in the retrieved patent documents; we also understand that the decrease or lack of patents from 2012 may be related to patent secrecy period. China is the leading country in the number of patents deafness and blindness, Japan turn the nation shows up with the most active organizations and the US have a situation of very broad inventive step. Brazil has great potential for development in TA in education, specifically for higher education, for it is a level of education that form human resources. We have seen what has been done to the National Survey on Assistive Technology through the Ministry of Science, Technology and Innovation and the Brazilian government has encouraged federal institutions to develop this technology to various areas of knowledge, as well as in the educational field; this brings business opportunities for inventors. It takes more detailed future studies for extending the scientific framework of this issue, thus contributing to fostering research on innovation and technology in Brazil.